Biton's Lost Siege Engine: Experimental archaeology in Classical Studies - Rademan, David John (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
This thesis entails an examination of several problems inherent in placing a technical treatise by the Hellenistic Greek engineer, Biton of Pergamon, at a siege of 156-154BCE, with a view to galvanising the existing case of previous scholarship through a combined approach of literary, textual, geographical, and technical analysis. Particular focus is given to the following problems: technical errors in current translations of the treatise of Biton; technical considerations in scholars' reproductions of a particular engine in the treatise; an assessment of the practical implications of the treatise in situ at the physical site of the ancient city of Pergamon in the second century BCE, as evidenced by archaeological findings and surveys; assessment of those implications by way of historical records of similar conflicts from the Hellenistic period; and suggesting a procedure of dimensional analysis for testing a hypothesis regarding the feasibility of the ancient engineer's recommended engines as a stand-in for the city's original defenses, in a manner that harmonises the methodologies of historicism and experimental archaeology with sound and appropriate modern engineering practice from the field of Fluid Mechanics.
Keywords: Pergamum (Extinct city); Dimensional analysis; Engineering -- History -- To 168 B.C.; Fluid mechanics -- History -- To 168 B.C.; Byzantine literature -- History and criticism; Siege warfare -- History -- To 168 B.C.; Biton of Pergamon; Isidorus of Abydos; Poliorcetics